Blowout and well control handbook - Grace, Robert D. (Amsterdam ; Boston : Gulf Professional Pub., 2003)
As with his 1994 book, Advanced Blowout and Well Control, Grace offers a book that presents tested practices and procedures for well control, all based on solid engineering principles and his own more than 25 years of hands-on field experience. Specific situations are reviewed along with detailed procedures to analyze alternatives and tackle problems. The use of fluid dynamics in well control, which the author pioneered, is given careful treatment, along with many other topics such as relief well operations, underground blowouts, slim hole drilling problems, and special services such as fire fighting, capping, and snubbing. In addition, case histories are presented, analyzed, and discussed. Provides new techniques for blowout containment, never before published, first used in the Gulf War. Provides the most up-to-date techniques and tools for blowout and well control. New case histories include the Kuwait fires that were set by Saddam Hussein during the Gulf War.
1. Equipment in Well Control -- 2. Classic Pressure Control Procedures While Drilling -- 3. Pressure Control Procedures While Tripping -- 4. Special Conditions, Problems, and Procedures in Well Control -- 5. Fluid Dynamics in Well Control -- 6. Special Services in Well Control -- 7. Relief Well Design and Operations -- 8. The Underground Blowout -- 9. The Al-Awda Project: The Oil Fires of Kuwait -- 10. Index.
Includes bibliographical references and index.
Keywords: Oil wells -- Blowouts -- Prevention; Oil fields -- Safety measures; Electronic books